2008
DOI: 10.1364/ol.33.002788
|View full text |Cite
|
Sign up to set email alerts
|

One-shot phase-shifting interferometry: five, seven, and nine interferograms

Abstract: To extract phase distributions, which evolve in time using phase-shifting interferometry, the simultaneous capture of several interferograms with a prescribed shift has to be done. Previous interferometric systems aimed to fulfill such a task were reported to get only four interferograms. It is pointed out that more than four suitable interferograms can be obtained with an interferometer that uses two windows in the object plane, a phase grid as a pupil, and modulation of polarization for each diffraction orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 4 publications
0
34
0
Order By: Relevance
“…(18) shows that the results are replicas of the pattern generated by the CSI displaced to the n th and l th orders of diffraction; each replica of the main pattern maintains an intensity modulated by Fourier Coefficients C n and C l corresponding to each direction. It should be noted that the contrast of the fringes depends on the degree of circular polarization of the interfering beams [Rodriguez, 2008]. In this case, the Ronchi gratings only multiplex the pattern, so the amplitudes of the orders only increase or decrease the intensity of the interference patterns, as it is shown in Fig.…”
Section: Interference Pattern Replicationmentioning
confidence: 96%
See 3 more Smart Citations
“…(18) shows that the results are replicas of the pattern generated by the CSI displaced to the n th and l th orders of diffraction; each replica of the main pattern maintains an intensity modulated by Fourier Coefficients C n and C l corresponding to each direction. It should be noted that the contrast of the fringes depends on the degree of circular polarization of the interfering beams [Rodriguez, 2008]. In this case, the Ronchi gratings only multiplex the pattern, so the amplitudes of the orders only increase or decrease the intensity of the interference patterns, as it is shown in Fig.…”
Section: Interference Pattern Replicationmentioning
confidence: 96%
“…Previous works have shown that when the interferometer is coupled to a 4-f system using phase grids, it is possible to obtain replicas of the interference pattern, and each one of these replicas can be modulated by polarization [Rodriguez 2008;Serrano, 2011]. A sinusoidal phase grid generated by the multiplication of two sinusoidal phase gratings, whose respective grating vectors are crossed, generates diffraction orders modulated by Bessel functions J q and J r [Rodriguez, 2008;, and the image of the interference pattern generated by the interferometer is found centered around each of them.…”
Section: Interferometer With Phase Gridsmentioning
confidence: 99%
See 2 more Smart Citations
“…a self-reference method is proposed for phase-shifting interferometry when translation and tilt errors exist. Another strategy to deal with this kind of problems can be using a one-shot phase-shifting interferometry method [9]. This approach allows recovering at the same time different interferograms at the camera detector.…”
Section: Introductionmentioning
confidence: 99%